Interleukin‐7 receptor blockade by an anti‐CD127 monoclonal antibody in nonhuman primate kidney transplantation. Issue 1 (14th August 2019) - Mai, Hoa Le; Nguyen, Thi Van Ha; Branchereau, Julien; Poirier, Nicolas; Renaudin, Karine; Mary, Caroline; Belarif, Lyssia; Minault, David; Hervouet, Jeremy; Le Bas‐Berdardet, Stéphanie; Soulillou, Jean‐Paul; Vanhove, Bernard; et al.
Abstract : IL‐7 is an important cytokine for T cell lymphopoiesis. Blockade of the IL‐7 signaling pathway has been shown to induce long‐term graft survival or graft tolerance in murine transplant models through inhibiting T cell homeostasis and favoring immunoregulation. In this study, we assessed for the first time the effects of a blocking anti‐human cluster of differentiation 127 (CD127) mAb administered in combination with low‐dose tacrolimus or thymoglobulin in a life‐sustaining kidney allograft model in baboons. Contrary to our expectation, the addition of an anti‐CD127 mAb to the treatment protocols did not prolong graft survival compared to low‐dose tacrolimus alone or thymoglobulin alone. Anti‐CD127 mAb administration led to full CD127 receptor occupancy during the follow‐up period. However, all treated animals lost their kidney graft between 1 week and 2 weeks after transplantation. Unlike in rodents, in nonhuman primates, anti‐CD127 mAb treatment does not decrease the absolute numbers of lymphocyte and lymphocyte subsets and does not effectively inhibit postdepletional T cell proliferation and homeostasis, suggesting that IL‐7 is not a limiting factor for T cell homeostasis in primates. Abstract : Although targeting the IL‐7 signaling pathway can prolong graft survival and even induce graft tolerance in murine allograft models, this study shows that IL‐7 receptor blockade by a humanized anti‐CD127 monoclonal antibody fails to improve kidney allograft survival in nonhuman primates, indicating differences in IL‐7 biology between mouse and primates.